Pembuatan Karbon Aktif Secara Kimia Hijau dari Tandan Sawit dengan Aktivasi Ultrasonik - Fatwa Insyirah; Miftahul Khair (Departemen Kimia FMIPA UNP, 2021)
Activated carbon from palm bunches by using ultrasonic assisted activation can increase the economic value of palm bunches. This study aims to determine the effect of the waves on the carbon produced and absorption of activated carbon as an adsorbent of lead metal ions (Pb2+). This study used the sonication method with ultrasonic wave activation. The variables observed were water content, ash content, volatile matter, fixed carbon and iodine absorption. Carbonization was conducted at mild condition of 300ºC for 60 minutes heating time. Ultrasonic irradiation (35 Watt, 40 KHz) for 15 minutes increases the carbon iodine number from 515.2358 mg/g up to 772.5459 which is higher than SNI 06-3730-1995 requirement of mg/ g 750 mg/g for activated carbon. FTIR spectra results show that activated carbon has -OH groups at wave numbers of 3000-3500 cm-1, C = C at wave numbers of 1550-1650 cm-1, CO at wave numbers of 1000-1260 cm-1 and CH at wave numbers of 810- 770 cm-1 . Adsorption test results showed that the prepared activated carbon was able to absorb Pb+2 ion at the optimum concentration of 40 mg/L. Adsorption isotherm study conducted by Freundlich equation produces a regression coefficient R2 = 0.4225 with a maximum absorption capacity of 7.4159 mg/ g.